From amines to (form)amides: a simple and successful mechanochemical approach - Casti, Federico; Mocci, Rita; Porcheddu, Andrea (Beilstein Journal of Organic Chemistry, 2022)
Two easily accessible routes for preparing an array of formylated and acetylated amines under mechanochemical conditions are presented. The two methodologies exhibit complementary features as they enable the derivatization of aliphatic and aromatic amines.
Keywords: acetamides; formamides; mechanochemistry; N-formylation; p-tosylimidazole